Quinolinol‐based Al/Triarylborane Dyad Assembly: Alteration of Electronic Transition States Mediated by Fluoride Anion Binding. (9th October 2018) - Lee, Ji Hye; Ryu, Chan Hee; Yu, Seokhyeon; Hwang, Hyonseok; Lee, Kang Mun
Abstract : In this study, we synthesized quinolinol‐ligand (2‐methylquinolin‐8‐ol, q)‐based aluminum complexes with phenyl (D1 ), biphenyl (D2 ), and naphthyl (D3 )‐bridged triarylboranes, and employed them as organometallic chemosensors for sensing mediated by fluoride anions. In addition, these dyad complexes were fully characterized by multinuclear nuclear magnetic resonance (NMR) spectroscopy and elemental analysis. UV/Vis titration experiments examining the association ofD1, D2, andD3 with fluoride demonstrated that the dyad complexes associated in a 1:1 binding stoichiometry in tetrahydrofuran (THF), with binding constants ( K ) in the range of 2.7–6.6 × 10 4 M −1 . Moreover, these dyad complexes showed a ratiometrically decreasing fluorescence response in photoluminescence titration experiments upon binding of fluoride to the borane moiety, thereby giving rise to a turn‐off chemosensor for detection of fluoride anions. It could be postulated that these turn‐off properties were caused by the interruption of the intramolecular charge‐transfer (ICT) transition between the q2 Al part and the bridged phenoxy groups. Furthermore, the theoretical calculation results for the dyad complexes and these fluoride adducts clearly indicate that the ICT transition between the q2 Al and bridged phenoxy groups of the complexes could be interrupted by the binding of fluoride to borane. Abstract :